Clinical applications of correlational vestibular autorotation test. (June 2015) - Hsieh, Li-Chun; Lin, Te-Ming; Chang, Yu-Min; Kuo, Terry B.J.; Lee, Gho-She
Abstract Conclusion: The correlational vestibular autorotation test (VAT) system has the advantages of good test–retest reliability and calibrations of absolute degrees of eye movement are unnecessary when acquiring a cross correlation coefficient (CCC). The approach is able to efficiently detect peripheral vestibulopathies. Objective: A VAT has some drawbacks including poor test–retest reliability and slippage of sensor. This study aimed to develop a correlational VAT system and to evaluate the reliability and applicability of this system. Methods: Twenty healthy participants and 10 vertiginous patients were enrolled. Vertical and horizontal autorotations from 0 to 3 Hz with either closed or open eyes were performed. A small sensor and a wireless transmission technique were used to acquire the electro-ocular graph and head velocity signals. The two signals were analyzed using CCCs to assess the functioning of the vestibular ocular reflex (VOR). Results: The results showed a significantly greater CCC for open-eye versus closed-eye of head autorotations. The CCCs also increased significantly with head rotational frequencies. Moreover, the CCCs significantly correlated with the VOR gains at autorotation frequencies ≥1.0 Hz. The test–retest reliability was good (intraclass correlation coefficients ≥0.85). The vertiginous participants had significantly lower individual CCCs and overall average CCC than age- and-gender matched controls.